The Existence of Complaint Offense Delict and Common Delict in Normative and Empirical Perspectives - Ferry Asril (PENA LAW: International Journal of Law, 2024)
Regulations regarding complaint offense delict and common delict in substantive criminal law in Indonesia are dependent on the type of delict. There are two types of delicts in relation to case processing, namely complaint offense delict and common delict. In common delict, the case can be processed without the consent of the victim. On the other hand, complaint offense delict is divided into absolute complaint offense delict and relative complaint offense delict. To determine whether a delict falls under complaint offense or common delict, it can be determined by reading the article or chapter in the Indonesian Criminal Code (KUHP) where the criminal act is stated. If the article or chapter does not state that it is a complaint offense, then it is considered a common delict, which must be prosecuted ex officio (without a complaint). Complaint offense delicts can result in undisclosed crimes, such as in Article 369 of the Criminal Code. Therefore, if the complaint offense delict in that article is treated as a common delict (not a complaint offense), the person who holds the secret may suffer further losses because their secret will be exposed. The victim must choose whether to file a complaint, risking the disclosure of their secret, or not. Therefore, this delict remains mostly hidden as a hidden crime. Another example is the potential disruption of someone's civil interests if a complaint offense, especially in cases of adultery, is treated as a common delict.